A Systematic Literature Study from 2013 to 2018: The Role of Knowledge in Open Innovation - Ganagambegai Laxamanan; Rabiah Eladwiah Abdul Rahim (International Review of Management and Marketing, 2020)
Knowledge plays a key role in the process of Open Innovation (OI). Nevertheless, by following the Knowledge Management (KM) lens OI has been barely examined. Therefore the aim of this paper is to provide a systematic review of the knowledge activities examined by previous literature to support OI results. The measures were taken to revise previous studies systematically in order to carry out a valuable literature review. After a collective analysis, we were able to garner a final review on 24articles. We subsequently identified and analyzed them by three major processes of OI. The findings enhanced the understanding of the various sources of knowledge practices and was able identify the best practices based on inbound, outbound and coupled processes to support OI activities. The empirical evidence found in the literature, highlights the shortcomings of the state-of-the-art and proposes possible avenues for studies. Despite knowledge being the most relevant resource integrated in OI activities, this is the first attempt to highlight how knowledge should be managed in an OI context by adopting knowledge lens. In addition to our research, we also recognize relevant topics that have been understudied so far which we are proposing as potential avenues for study. Keywords: Open Innovation, Closed Innovation, In-bound Open Innovation, Outbound Open Innovation, Knowledge Management.